2020
DOI: 10.1101/2020.09.30.321661
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improved protein model quality assessment by integrating sequential and pairwise features using deep learning

Abstract: Motivation: Accurately estimating protein model quality in the absence of experimental structure is not only important for model evaluation and selection, but also useful for model refinement. Progress has been steadily made by introducing new features and algorithms (especially deep neural networks), but accuracy of quality assessment (QA) is still not very satisfactory, especially local QA on hard protein targets. Results: We propose a new single-model-based QA method ResNetQA for both local and global quali… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 43 publications
(54 reference statements)
0
18
0
Order By: Relevance
“…The benchmark dataset of geometries prediction network was constructed from SCOPe 2.07 (Fox et al, 2014) (deposited by November 30, 2018). To train the geometric constraints prediction neural network, the sequences with the sequence similarity of more than 40% with the dataset of model evaluation network are eliminated by CD-HIT-2D (Jing et al, 2020), and 166,025 sequences are retained. Then, the remaining sequences are limited to 50 to 500 residues and clustered by CD-HIT (Fu et al, 2012) with 30% sequence similarity to generate 9,091 representatives.…”
Section: Methodsmentioning
confidence: 99%
“…The benchmark dataset of geometries prediction network was constructed from SCOPe 2.07 (Fox et al, 2014) (deposited by November 30, 2018). To train the geometric constraints prediction neural network, the sequences with the sequence similarity of more than 40% with the dataset of model evaluation network are eliminated by CD-HIT-2D (Jing et al, 2020), and 166,025 sequences are retained. Then, the remaining sequences are limited to 50 to 500 residues and clustered by CD-HIT (Fu et al, 2012) with 30% sequence similarity to generate 9,091 representatives.…”
Section: Methodsmentioning
confidence: 99%
“…In the 13th Critical Assessment of Protein Structure Prediction (CASP13), the inter-residue contact information and deep learning were the key for DeepRank 1 to achieve the best performance in ranking protein structural models with the minimum loss of GDT-TS score 2 . Recently, inter-residue distance predictions have been used with deep learning for the estimation of model accuracy 3,4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Treating a protein structural model as a graph, ProteinGCN [13], GraphQA [14] and VoroCNN [15] applied graph convolutional networks (GCN) to estimate the model accuracy. ResNetQA [16] and DeepAccNet [17] used deep residue networks to address the problem.…”
Section: Introductionmentioning
confidence: 99%
“…In CSAP13, DeepRank [5] demonstrated that accurate residueresidue contacts (a simplified representation of distances between residues) predicted by deep learning improved the prediction of the quality of protein structural models, suggesting that more detailed residue-residue distance predictions could further improve EMA. However, only a few methods [6], [16], [17], use residue-residue distances to estimate the accuracy of protein structural models.…”
Section: Introductionmentioning
confidence: 99%